High throughput screening and evaluation of salt-tolerant mutants from an EMS collection of Cucurbita pepo - Alonso, Sonsoles; Gautam, Keshav; Iglesias-Moya, Jessica; Segura, María; Rebolloso, María del Mar; Salas-Sanjuán, María del Carmen; Martínez, Cecilia; Jamilena, Manuel (Frontiers in Plant Science, 2025)
Salinity is a major environmental stress limiting crop growth and yield in many arid and semi-arid regions of the world. In this study, we used a germination-based selection method to screen an EMS collection of Cucurbita pepo, consisting of 3,751 M2 lines, for salt tolerance. The screening resulted in the identification of six salt-tolerant mutants that exhibited enhanced germination and plant growth under salt stress conditions. This enhanced salt tolerance was found to be associated with increased production of proline, soluble sugars, and anthocyanins, which are known to exert osmoprotective and ROS scavenging functions. The mutant lines TS-1378 and TS-2075 were selected to be tested as rootstocks and showed a positive effect on the vegetative growth of scions under standard and saline conditions. In conclusion, the research provides an efficient protocol for high throughput screening for salt tolerance, novel useful mutants to study the mechanism behind salt tolerance, and valuable genetic resources for pumpkin breeding.